Robotics and Mechatronics Proceedings of the 4th IFToMM International Symposium on Robotics and Mechatronics - Zeghloul, Saïd.; Laribi, Med Amine; Gazeau, Jean-Pierre.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This volume contains papers that have been selected after review for oral presentation at ISRM 2015, the Fourth IFToMM International Symposium on Robotics and Mechatronics held in Poitiers, France 23-24 June 2015. These papers  provide a vision of the evolution of the disciplines of robotics and mechatronics, including but not limited to: mechanism design; modeling and simulation; kinematics and dynamics of multibody systems; control methods; navigation and motion planning; sensors and actuators; bio-robotics; micro/nano-robotics; complex robotic systems; walking machines, humanoids-parallel kinematic structures: analysis and synthesis; smart devices; new design; application and prototypes. The book can be used by researchers and engineers in the relevant areas of robotics and mechatronics.
Part I: Mechanism and advanced mechanical design -- A study of structural stress analysis of reducers for supporting reliability design, by Yuo-Tern Tsai, Kuan-Hong Lin, Kuo-Shong Wang -- Structural and Dimensional Synthesis of Parallel Mechanism with Two End-Effectors, by Zh. Baigunchekov, M. Kalimoldaev, M. Utenov, B. Arymbekov, N. Baigunchekov -- Parametric Design Optimization of Two Link Robotic Manipulator, by F. Z. Baghli, L. El Bakkali, O. Hamdoun -- Investigation of the Behaviour of a new Miniature Carbon-Paraffin Phase-change  Actuator, by P. Lazarou, C. Rotinat-Libersa -- Synthesis of driving mechanisms in robotics by combinatorial analysis method, by Peter Mitrouchev, Jingtao Chen, Frédéric Maffray, Yaqing Zheng -- Part II: Humanoid and legged robotics -- Design and experiments on a new humanoid robot: TIDOM, by A. Eon, P. Seguin, M. Arsicault, S. Zeghloul -- Experimental Inspiration and Rapid Prototyping of a novel Humanoid Torso, by D. Cafolla, M. Ceccarelli -- Design of Robots Used As Education Companion and Tutor, by Albert Causo, Giang Truong Vo, I-Ming Chen, Song Huat Yeo -- Walking of a biped robot balanced with a reciprocating torso, by Victor De-Léon-Gomez, J. Alfonso Pamanes, Victor Santibanez -- Part III: Parallel manipulators -- Determining the reachable workspace for 6-DOF Delta manipulators, by C. K. Huang, K. Y. Tsai -- A reconfiguration strategy of a parallel Delta-type robot to improve the kinematic performance, by A. L. Balmaceda-Santamaria, E. Castillo-Castaneda.-  Workspace and Singularity analysis of a Delta like family robot, by R. Jha, D. Chablat, F. Rouillier, G. Moroz -- Optimal trajectory Planning of 3RRR Parallel Robot using ant colony algorithm, by O. Hamdoun, L. El Bakkali, F. Z. Baghli -- Part IV: Medical robotics I -- Force control implementation of a haptic device for medical use, by H. Saafi, M.A. Laribi, S. Zeghloul -- Integration of Automated Camera Steering for RoboticSingle-Site Surgery, by  Mohsen Zahiri, Carl A. Nelson, R. Gonzalo Garay-Romero, Dmitry Oleynikov -- Kinematic models of a new spherical parallel manipulator used as a master device, by H. Saafi, M.A. Laribi, M. Arsicault, S. Zeghloul -- Part V: Medical robotics II: Mechatronic device to assist therapies during hand fingers rehabilitation, by F. Aguilar-Pereyra, E. Castillo-Castaneda -- Mechanical Design of a Craniotomy Robotic Manipulator Based on Optimal Kinematic and Force Performance, by T. Essomba, C.-T. Wu, S.-T. Lee, C.-H. Kuo -- Dynamic Simulation of a Cable-Based Gait Training Machine, by H. Lamine, S. Bennour, L. Romdhane -- An in vivo experiment to assess the validity of the Log Linearized Hunt-Crossley model for contacts of robots with the human abdomen, by F. Courrèges, M. A. Laribi, M. Arsicault, S. Zeghloul -- Part VI: Control and vision; Real-time Reconstruction of Heightmaps from Images taken with a UAV, by Jose Gabriel Ramirez-Torres, Ander Larranaga-Cepeda -- A Human-Machine Interface with Unmanned Aerial Vehicles, by D. Soto-Gerrero, J.-G. Ramrez-Torres -- Design and Simulation of Robot Manipulator Position Control System based on Adaptive Fuzzy PID Controller, by F. Z. Baghli, L. El Bakkali -- Generating the optimum dynamic trajectory of a hybrid cable-serial robot, by M. Ismail, S. Lahouar, L. Romdhane -- An Integrated Software Package for Advanced Industrial Robot Application, by C. Liang, H. Yan, R. Li, I.-M. Chen, M.H. Ang Jr., Z. Huang -- Part VII: Advanced Robotics -- A method for the approximation of the multiple IK solutions of regular manipulators based on the uniqueness domains and using MLP, by  Vassilis C. Moulianitis, Evgenios M. Kokkinopoulos, Nikos A. Aspragathos -- An Approach to Symbolical Formulation of Forward Kinematics of Serial Robots, by S. Krutikov -- Grasps Database Generator for Anthropomorphic Robotic Hands, by H. Mnyusiwalla, P. Vulliez, J.P. Gazeau, S. Zeghloul -- From human motion capture toindustrial robot imitation, by  P. Laguillaumie, M. A. Laribi, P. Seguin, P. Vulliez, A. Decatoire, S. Zeghloul -- Dynamic decoupling of adjustable serial manipulators taking into account the changing payload, by J. Xu, V. Arakelian, J.-P. Le Baron -- Author Index.
Keywords: Mechatronics; Engineering design; Microtechnology; Microelectromechanical systems; Mechatronics; Engineering Design; Microsystems and MEMS